Path to the Universal Self in Haji Baktash Walî: Four Doors - Forty Stations - Erdem Sevim (Spiritual Psychology and Counseling)
This work aims to discover the shared psychological characteristics between Haji Bektash Walî’s desire to “be in a state of unity,” as described in his teaching of “Four Doors – Forty Stations (Dört Kapı Kırk Makâm),” and the concept of the “universal self” appearing in humanist psychology’s emphasis on humans’ “transcendental need.” In connection with these two concepts, this work will search out the similarities between the Sufi notion of reaching one’s God-created human perfection (insân-i kâmil) and humanist psychology’s concept of self-actualization. In Turkey, Haji Baktash Walî is not only the symbol of folk Sufism, itself founded on peace, love, and acceptance, but also a true man of hearts. This article not only examines the states (ahwâl) experienced while on a spiritual journey toward reaching the universal self are evaluated in light of these two approaches, but also the similarities between peak experiences and mystical experiences and the change and transformation they lead to in one’s character.